A dual‐polarized antenna with low cross polarization, high gain, and isolation for the fifth‐generation array/multiple‐input multiple‐output communications. Issue 2 (21st May 2020) - Feng, Botao; Luo, Tao; Zhou, Tian; Sim, Chow‐Yen‐Desmond
Abstract: A dual‐polarized antenna for the fifth‐generation (5G) array/massive multiple‐input multiple‐output (MIMO) communications is proposed in this paper. Through combining dual‐polarized differentially feeding structure and complementary magneto‐electric (ME) dipole antenna, low cross polarization (X‐pol), high gain, and isolation characteristics can be achieved by the antenna element. To take advantage of these characteristics in the array, a modified 1‐to‐16‐way H‐shaped differentially feeding network is designed to feed the 16‐element antenna array. Here, vertical cross‐shaped patches with dotted slots are arranged between adjacent ME‐dipole antenna elements to further improve the array isolation. By removing the H‐shaped differentially feeding network and the substrate at the bottom, a high‐capacity MIMO antenna system can be achieved. Measured results show that low X‐pol level of −35.7 dB and high gain of larger than 8.1 dBi can be attained by the antenna elements across the 5G frequency bands (3.3‐5.1 GHz). In addition, the antenna array has exhibited high gain of 17.3 dBi and the MIMO antenna has realized very low envelope correlation coefficient of 0.004.